Correlates of job satisfaction its implication to educational administration - Hilario, Jose T. (2008)
This qualitative study investigated the relationship of teachers' socio-demographic traits, behavioural traits, psychological traits, work description, and stress condition to teachers' job satisfaction. The study used a 13-part survey questionnaires developed by the researcher. Descriptive statistics, factor analysis and correlation analysis were also used. The results showed that the respondent public elementary school teachers have moderate satisfaction wtih their jobs. It was concluded that teachers with no intention of leaving the country are less obedient on the job, have personal work ethics, are given feedbacks on the job, are aware of company rules and regulations, and are experiencing burnout, are the ones who are satisfied with their job.
Thesis (M.A. Educational Administration)--University of the Philippines, Diliman.
Keywords: Elementary school teachers -- Job satisfaction -- Philippines -- Quezon City; School management and organization -- Philippines -- Quezon City; Public schools -- Philippines -- Quezon City -- Administration; Education, Elementary -- Philippines -- Quezon City